Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Recent insights in the development and functions of insect hemocytes - Michael R Strand (Current Opinion in Insect Science, 2026)

Genome Variation in Three Anthophora Bee Species Reflects Divergent Demographic Histories - Demetris Taliadoros; André E. R. Soares; Guilherme Dias; Ignas Bunikis; Martin Pippel; Anna Olsson; Mai‐Britt Mosbech; Julia Heintz; Nina Lager; Anna‐Sofi Strand; Mats Pettersson; Olga Vinnere Pettersson; et al. (Molecular Ecology, 2025)
Population genomics can reveal trends and drivers of biodiversity loss, but it is still unclear how best to use measures of genome variation to understand population vulnerability in insects. Here we study genome variation in three species of Anthophora bees that show contrasting population trends in northern Europe. Two species, Anthophora plagiata and Anthophora retusa , have experienced declines and recoveries of different magnitudes in the last 50 years, whereas a third species, Anthophora quadrimaculata , has relative population stability. We generate highly contiguous genome assemblies and use them to study genome variation in 136 samples of these species collected throughout Sweden. We find exceedingly low genetic variation in A. plagiata , which has experienced a severe recent bottleneck, but high genetic variation in A. retusa , despite a similar recent population trajectory. Fragmented populations of the threatened species A. plagiata appear isolated from each other, but in A. retusa , there is a lack of deep population structure among geographically separated subpopulations. We infer population size in the distant past using MSMC2 and recent past using GONE. These methods are remarkably concordant and indicate ancient fluctuations in population size dating back to the Pleistocene, with moderate expansions in the past century in all three species. These results are comparable to some other studies of endangered insects, which have experienced population declines that predate the modern era. We detect long blocks of identity‐by‐state in A. plagiata , indicative of severe recent inbreeding. Translocations between isolated populations of this species could have a positive effect on their resilience.

The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Piloting a culturally significant areas framework for spatial planning and management in the coastal environment of South Africa - Loyiso V. Dunga; Kerry J. Sink; Megan G. Van der Bank; Linda R. Harris; Lara Van Niekerk; Myriam Perschke; Ruan Brand; Judy Mann-Lang; Mike Bruton; Mia Strand; Nina Rivers; Stephen Lamberth; et al. (Marine Policy, 2025)

Trend analyses of persistent organic pollutants in human milk from first-time mothers in Norway between 2002 and 2021 - Kristina R. Nermo; Kjersti S. Bakken; Jan L. Lyche; Anuschka Polder; Aina Jansen; Siri Kaldenbach; Gabrielle Haddad-Weiser; Tor A. Strand; Merete Å. Eggesbø (International Journal of Hygiene and Environmental Health, 2025)

Physiological trade-offs in male social insects: Interactions among infection, immunity, fertility, size, and age in honey bee drones - Bradley N. Metz; Tatiana Molina-Marciales; Micheline K. Strand; Olav Rueppell; David R. Tarpy; Esmaeil Amiri (Journal of Insect Physiology, 2024)

Perinatal exposure to environmental chemicals that disrupt thyroid function can perturb testis development - Monica K. Draskau; Ida W. Strand; Raul Ayala Davila; Anne-Sofie R. Ballegaard; Mikael Pedersen; Louise Ramhøj; Sofie Rising; Kieu-mi Tran; Marta Axelstad; Josephine Bowles; Anna K. Rosenmai; Cassy M. Spiller; et al. (Environmental Pollution, 2024)

Variations in the chemical composition of Norwegian cultivated brown algae Saccharina latissima and Alaria esculenta based on deployment and harvest times - Øystein Arlov; Katharina Nøkling-Eide; Olav Andreas Aarstad; Synnøve Strand Jacobsen; Anne-Mari Langeng; Ana R. Borrero-Santiago; Maren Sæther; Turid Rustad; Finn Lillelund Aachmann; Håvard Sletta (Algal Research, 2024)

Integrative demographic modelling reduces uncertainty in estimated rates of species' historical range shifts - Antonio R. Castilla; Alissa Brown; Sean Hoban; Everett Andrew Abhainn; John D. Robinson; Jeanne Romero‐Severson; Adam B. Smith; Allan E. Strand; John R. Tipton; Andria Dawson (Journal of Biogeography, 2024)
Aim Biogeographers have used three primary data types to examine shifts in tree ranges in response to past climate change: fossil pollen, genetic data and contemporary occurrences. Although recent efforts have explored formal integration of these types of data, we have limited understanding of how integration affects estimates of range shift rates and their uncertainty. We compared estimates of biotic velocity (i.e. rate of species' range shifts) using each data type independently to estimates obtained using integrated models. Location Eastern North America. Taxon Fraxinus pennsylvanica Marshall (green ash). Methods Using fossil pollen, genomic data and modern occurrence data, we estimated biotic velocities directly from 24 species distribution models (SDMs) and 200 pollen surfaces created with a novel Bayesian spatio‐temporal model. We compared biotic velocity from these analyses to estimates based on coupled demographic‐coalescent simulations and Approximate Bayesian Computation that combined fossil pollen and SDMs with population genomic data collected across the F. pennsylvanica range. Results Patterns and magnitude of biotic velocity over time varied by the method used to estimate past range dynamics. Estimates based on fossil pollen yielded the highest rates of range movement. Overall, integrating genetic data with other data types in our simulation‐based framework reduced apparent uncertainty in biotic velocity estimates and resulted in greater similarity in estimates between SDM‐ and pollen‐integrated analyses. Main Conclusions By reducing uncertainty in our assessments of range shifts, integration of data types improves our understanding of the past distribution of species. Based on these results, we propose further steps to reach the integration of these three lines of biogeographical evidence into a unified analytical framework.

Insulin-like peptides and ovary ecdysteroidogenic hormone differentially stimulate physiological processes regulating egg formation in the mosquito Aedes aegypti - Kangkang Chen; Xiaoyi Dou; Jai Hoon Eum; Ruby E. Harrison; Mark R. Brown; Michael R. Strand (Insect Biochemistry and Molecular Biology, 2023)

An aphid symbiont confers protection against a specialized RNA virus, another increases vulnerability to the same pathogen - Clesson H. V. Higashi; William L. Nichols; Germain Chevignon; Vilas Patel; Suzanne E. Allison; Kyungsun Lee Kim; Michael R. Strand; Kerry M. Oliver (Molecular Ecology, 2023)
Insects often harbour heritable symbionts that provide defence against specialized natural enemies, yet little is known about symbiont protection when hosts face simultaneous threats. In pea aphids ( Acyrthosiphon pisum ), the facultative endosymbiont Hamiltonella defensa confers protection against the parasitoid, Aphidius ervi , and Regiella insecticola protects against aphid‐specific fungal pathogens, including Pandora neoaphidis . Here, we investigated whether these two common aphid symbionts protect against a specialized virus A . pisum virus (APV), and whether their antifungal and antiparasitoid services are impacted by APV infection. We found that APV imposed large fitness costs on symbiont‐free aphids and these costs were elevated in aphids also housing H . defensa . In contrast, APV titres were significantly reduced and costs to APV infection were largely eliminated in aphids with R . insecticola . To our knowledge, R . insecticola is the first aphid symbiont shown to protect against a viral pathogen, and only the second arthropod symbiont reported to do so. In contrast, APV infection did not impact the protective services of either R . insecticola or H . defensa . To better understand APV biology, we produced five genomes and examined transmission routes. We found that moderate rates of vertical transmission, combined with horizontal transfer through food plants, were the major route of APV spread, although lateral transfer by parasitoids also occurred. Transmission was unaffected by facultative symbionts. In summary, the presence and species identity of facultative symbionts resulted in highly divergent outcomes for aphids infected with APV, while not impacting defensive services that target other enemies. These findings add to the diverse phenotypes conferred by aphid symbionts, and to the growing body of work highlighting extensive variation in symbiont‐mediated interactions.

Cardiomyocyte-specific overexpression of syndecan-4 in mice results in activation of calcineurin-NFAT signalling and exacerbated cardiac hypertrophy - Ida G. Lunde; J. Magnus Aronsen; A. Olav Melleby; Mari E. Strand; Jonas Skogestad; Bård A. Bendiksen; M. Shakil Ahmed; Ivar Sjaastad; Håvard Attramadal; Cathrine R. Carlson; Geir Christensen (Molecular Biology Reports, 2022)
Background Cardiomyocyte hypertrophy is a hallmark of cardiac dysfunction in patients with aortic stenosis (AS), and can be triggered by left ventricular (LV) pressure overload in mice by aortic banding (AB). Syndecan-4 is a transmembrane heparan sulphate proteoglycan which is found increased in the myocardium of AS patients and AB mice. The role of syndecan-4 in cardiomyocyte hypertrophy is not well understood. Purpose of the study We developed mice with cardiomyocyte-specific overexpression of syndecan-4 ( Sdc4-Tg ) and subjected these to AB to examine the role of syndecan-4 in hypertrophy and activation of the pro-hypertrophic calcineurin-NFAT signalling pathway. Methods and results Sdc4-Tg mice showed exacerbated cardiac remodelling upon AB compared to wild type (WT). At 2–6 weeks post-AB, Sdc4-Tg and WT mice showed similar hypertrophic growth, while at 20 weeks post-AB, exacerbated hypertrophy and dysfunction were evident in Sdc4-Tg mice. After cross-breeding of Sdc4-Tg mice with NFAT-luciferase reporter mice, we found increased NFAT activation in Sdc4-Tg hearts after AB. Immunoprecipitation showed that calcineurin bound to syndecan-4 in Sdc4-Tg hearts. Isolated cardiomyocytes from Sdc4-Tg mice showed alterations in Ca 2+ fluxes, suggesting that syndecan-4 regulated Ca 2+ levels, and thereby, activating the syndecan-4-calcineurin complex resulting in NFAT activation and hypertrophic growth. Similarly, primary cardiomyocyte cultures from neonatal rats showed increased calcineurin-NFAT-dependent hypertrophic growth upon viral Sdc4 overexpression. Conclusion Our study of mice with cardiomyocyte-specific overexpression of Sdc4 have revealed that syndecan-4 is important for activation of the Ca 2+ -dependent calcineurin-NFAT signalling pathway, hypertrophic remodelling and dysfunction in cardiomyocytes in response to pressure overload.

Hypoxia constrains behavioral responses to chemical alarm cues by fathead minnows Pimephales promelas - Madisen C. Strand; Isabel G. DeVriendt; Alex R. Seigel; Christopher L. Merkord; Brian D. Wisenden (Environmental Biology of Fishes, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Association of predation risk with a heterospecific vocalization by an anabantoid fish - Alex R. Seigel; Isabel G. DeVriendt; Madisen C. Strand; Ananda Shastri; Brian D. Wisenden (Journal of Fish Biology, 2022)
Honey gouramis ( Trichogaster chuna ) received chemical alarm cues derived from conspecific epidermal tissue and, simultaneously, the vocalization produced by a heterospecific gourami species, the sparkling pygmy gourami ( Trichopsis pumila ). Control trials paired water with the vocalization. In trials that received alarm cues, honey gouramis significantly increased activity relative to control trials that received water, suggesting an attempt to flee and search for refuge. When the recording of the vocalization was later replayed to test fish without any additional chemical cue, fish that had previously experienced the alarm cue froze while those that had received water with the vocalization did not change their behaviour. These data indicate that honey gouramis recognize and respond to chemical alarm cues, making this report the second anabantoid species to be recorded with this response. Second, these data indicate that honey gouramis can associate risk of predation with a novel auditory stimulus, including vocalizations from other species. These data suggest the potential for vocalizations to evolve into alarm signals in this group of fishes.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Trichoplusia ni and Chrysodeixis includens larvae show different susceptibility to Chrysodeixis includens single nucleopolyhedrovirus per os infection - Fabricio da Silva Morgado; Leonardo Assis Silva; Laryssa Moreira Bernardes; Cecilia Czepak; Michael R. Strand; Bergmann Morais Ribeiro (Journal of Pest Science, 2020)

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

Uncertainty Quantification and Sensitivity Analysis for Computational FFR Estimation in Stable Coronary Artery Disease - Fredrik E. Fossan; Jacob Sturdy; Lucas O. Müller; Andreas Strand; Anders T. Bråten; Arve Jørgensen; Rune Wiseth; Leif R. Hellevik (Cardiovascular Engineering and Technology, 2018)

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Mosquitoes host communities of bacteria that are essential for development but vary greatly between local habitats - Kerri L. Coon; Mark R. Brown; Michael R. Strand (Molecular Ecology, 2016)
Mosquitoes are insects of interest because several species vector disease‐causing pathogens to humans and other vertebrates. We previously reported that mosquitoes from long‐term laboratory cultures require living bacteria in their gut to develop, but development does not depend on particular species of bacteria. Here, we focused on three distinct but interrelated areas of study to better understand the role of bacteria in mosquito development by studying field and laboratory populations of Aedes aegypti , Aedes albopictus and Culex quinquefasciatus from the southeastern United States. Sequence analysis of bacterial 16S rRNA gene amplicons showed that bacterial community composition differed substantially in larvae from different collection sites, whereas larvae from the same site shared similarities. Although previously unknown to be infected by Wolbachia , results also indicated that Ae. aegypti from one field site hosted a dual infection. Regardless of collection site or factors like Wolbachia infection, however, each mosquito species required living bacteria in their digestive tract to develop. Results also identified several concerns in using antibiotics to eliminate the bacterial community in larvae in order to study its developmental consequences. Altogether, our results indicate that several mosquito species require living bacteria for development. We also hypothesize these species do not rely on particular bacteria because larvae do not reliably encounter the same bacteria in the aquatic habitats they develop in.

A first report on coexistence and hybridization of Mytilus trossulus and M. edulis mussels in Greenland - R. Wenne; L. Bach; M. Zbawicka; J. Strand; J. H. McDonald (Polar Biology, 2016)

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Mosquitoes rely on their gut microbiota for development - Kerri L. Coon; Kevin J. Vogel; Mark R. Brown; Michael R. Strand (Molecular Ecology, 2014)
Field studies indicate adult mosquitoes ( C ulicidae) host low diversity communities of bacteria that vary greatly among individuals and species. In contrast, it remains unclear how adult mosquitoes acquire their microbiome, what influences community structure, and whether the microbiome is important for survival. Here, we used pyrosequencing of 16S r RNA to characterize the bacterial communities of three mosquito species reared under identical conditions. Two of these species, A edes aegypti and A nopheles gambiae , are anautogenous and must blood‐feed to produce eggs, while one, G eorgecraigius atropalpus , is autogenous and produces eggs without blood feeding. Each mosquito species contained a low diversity community comprised primarily of aerobic bacteria acquired from the aquatic habitat in which larvae developed. Our results suggested that the communities in A e. aegypti and A n. gambiae larvae share more similarities with one another than with G . atropalpus . Studies with A e. aegypti also strongly suggested that adults transstadially acquired several members of the larval bacterial community, but only four genera of bacteria present in blood fed females were detected on eggs. Functional assays showed that axenic larvae of each species failed to develop beyond the first instar. Experiments with A e. aegypti indicated several members of the microbial community and E scherichia coli successfully colonized axenic larvae and rescued development. Overall, our results provide new insights about the acquisition and structure of bacterial communities in mosquitoes. They also indicate that three mosquito species spanning the breadth of the C ulicidae depend on their gut microbiome for development.

Long‐term dynamics of mycorrhizal root tips in a loblolly pine forest grown with free‐air CO 2 enrichment and soil N fertilization for 6 years - Seth G. Pritchard; Benton N. Taylor; Emily R. Cooper; Katilyn V. Beidler; Allan E. Strand; M. Luke McCormack; Siyao Zhang (Global Change Biology, 2014)
Large‐scale, long‐term FACE (Free‐Air CO 2 enrichment) experiments indicate that increases in atmospheric CO 2 concentrations will influence forest C cycling in unpredictable ways. It has been recently suggested that responses of mycorrhizal fungi could determine whether forest net primary productivity ( NPP ) is increased by elevated CO 2 over long time periods and if forests soils will function as sources or sinks of C in the future. We studied the dynamic responses of ectomycorrhizae to N fertilization and atmospheric CO 2 enrichment at the Duke FACE experiment using minirhizotrons over a 6 year period (2005–2010). Stimulation of mycorrhizal production by elevated CO 2 was observed during only 1 (2007) of 6 years. This increased the standing crop of mycorrhizal tips during 2007 and 2008; during 2008, significantly higher mortality returned standing crop to ambient levels for the remainder of the experiment. It is therefore unlikely that increased production of mycorrhizal tips can explain the lack of progressive nitrogen limitations and associated increases in N uptake observed in CO 2 ‐enriched plots at this site. Fertilization generally decreased tree reliance on mycorrhizae as tip production declined with the addition of nitrogen as has been shown in many other studies. Annual NPP of mycorrhizal tips was greatest during years with warm January temperatures and during years with cool spring temperatures. A 2 °C increase in average late spring temperatures (May and June) decreased annual production of mycorrhizal root tip length by 50%. This has important implications for ecosystem function in a warmer world in addition to potential for forest soils to sequester atmospheric C.

Systematic analysis of a wasp parasitism arsenal - Gaelen R. Burke; Michael R. Strand (Molecular Ecology, 2014)
Parasitoid wasps are among the most diverse insects on earth with many species causing major mortality in host populations. Parasitoids introduce a variety of factors into hosts to promote parasitism, including symbiotic viruses, venom, teratocytes and wasp larvae. Polydnavirus‐carrying wasps use viruses to globally suppress host immunity and prevent rejection of developing parasites. Although prior results provide detailed insights into the genes viruses deliver to hosts, little is known about other products. RNA seq and proteomics were used to characterize the proteins secreted by venom glands, teratocytes and larvae from M icroplitis demolitor, which carries M . demolitor bracovirus (Md BV ). These data revealed that venom glands and teratocytes secrete large amounts of a small number of products relative to ovaries and larvae. Venom and teratocyte products exhibited almost no overlap with one another or Md BV genes, which suggested that M . demolitor effector molecules are functionally partitioned according to their source. This finding was well illustrated in the case of Md BV and teratocytes. Many viral proteins have immunosuppressive functions that include disruption of antimicrobial peptide production, yet this study showed that teratocytes express high levels of the antimicrobial peptide hymenoptaecin, which likely compensates for Md BV ‐mediated immunosuppression. A second key finding was the prevalence of duplications among genes encoding venom and teratocyte molecules. Several of these gene families share similarities with proteins from other species, while also showing specificity of expression in venom glands or teratocytes. Overall, these results provide the first comprehensive analysis of the proteins a polydnavirus‐carrying wasp introduces into its host.

Sampling volume in root studies: the pitfalls of under‐sampling exposed using accumulation curves - Benton N. Taylor; Katilyn V. Beidler; Emily R. Cooper; Allan E. Strand; Seth G. Pritchard (Ecology Letters, 2013)
Root systems are important for global models of below‐ground carbon and nutrient cycling. Notoriously difficult sampling methods and the fractal distribution of root diameters in the soil make data being used in these models especially susceptible to error resulting from under‐sampling. We applied the concept of species accumulation curves to root data to quantify the extent of under‐sampling inherent to minirhizotron and soil coring sampling for both root uptake and carbon content studies. Based on differences in sample size alone, minirhizotron sampling missed approximately one third of the root diameters observed by soil core sampling. Sample volumes needed to encounter 90% of root diameters averaged 2481 cm 3 for uptake studies and 5878 cm 3 for root carbon content studies. These results show that small sample volumes encounter a non‐representative sample of the overall root pool, and provide future guidelines for determining optimal sample volumes in root studies.

Impact of early salmon louse, L epeophtheirus salmonis , infestation and differences in survival and marine growth of sea‐ranched A tlantic salmon, S almo salar L., smolts 1997–2009 - O T Skilbrei; B Finstad; K Urdal; G Bakke; F Kroglund; R Strand (Journal of Fish Diseases, 2013)
The impact of salmon lice on the survival of migrating A tlantic salmon smolts was studied by comparing the adult returns of sea‐ranched smolts treated for sea lice using emamectin benzoate or substance EX with untreated control groups in the R iver D ale in western N orway. A total of 143 500 smolts were released in 35 release groups in freshwater from 1997 to 2009 and in the fjord system from 2007 to 2009. The adult recaptures declined gradually with release year and reached minimum levels in 2007. This development corresponded with poor marine growth and increased age at maturity of ranched salmon and in three monitored salmon populations and indicated unfavourable conditions in the N orwegian S ea. The recapture rate of treated smolts was significantly higher than the controls in three of the releases performed: the only release in 1997, one of three in 2002 and the only group released in sea water in 2007. The effect of treating the smolts against salmon lice was smaller than the variability in return rates between release groups, and much smaller that variability between release years, but its overall contribution was still significant ( P 0.05) and equivalent to an odds ratio of the probability of being recaptured of 1.17 in favour of the treated smolts. Control fish also tended to be smaller as grilse ( P = 0.057), possibly due to a sublethal effect of salmon lice.

Oxidative stress protection and the repair response to hydrogen peroxide in the hyperthermophilic archaeon Pyrococcus furiosus and in related species - Kari R. Strand; Chengjun Sun; Ting Li; Francis E. Jenney; Gerrit J. Schut; Michael W. W. Adams (Archives of Microbiology, 2010)

Mycorrhizal and rhizomorph dynamics in a loblolly pine forest during 5 years of free‐air‐CO 2 ‐enrichment - S. G. PRITCHARD; A. E. STRAND; M. L. McCORMACK; M. A. DAVIS; R. OREN (Global Change Biology, 2008)
Soil fungi couple plant and ecosystem resource demands to pools of soil resources. Research on these organisms is needed to predict how rising atmospheric CO 2 will influence forest ecosystem processes and soil carbon (C) sequestration potential. We examined the influence of free‐air‐CO 2 ‐enrichment (FACE) on mycorrhizal and extraradical rhizomorph dynamics over a 5‐year period in a loblolly pine forest using minirhizotrons. Standing crop of mycorrhizal root tips varied greatly spatially and through time. Summed across all years, CO 2 enrichment increased mycorrhizal root tip production by 194% in deep soil (15–30 cm) but did not influence mycorrhizal production in shallow soil (0–15 cm). Production and mortality of soil rhizomorph length was 27% and 25% greater in CO 2 ‐enriched plots compared with controls over a 5‐year period beginning in January of 2000 and running through autumn 2004. Effects of atmospheric CO 2 enrichment on longevity of mycorrhizal root tips and rhizomorphs varied with soil depth (mycorrhizae and rhizomorphs) and with diameter (rhizomorphs). For instance, survival of mycorrhizal tips was reduced in CO 2 ‐enriched plots in deep soil (15–30 cm depth) but was increased in shallower soil (0–15 cm). Rhizomorph turnover was accelerated in shallow soil but effects on survivorship in deep soil varied according to diameter. A drought in 2002 coupled with loss of leaf area to an ice storm late in 2002 were followed by reductions in rhizomorph and mycorrhizal production, increases in mortality, and decreases in standing crop during 2003 and 2004. These effects tended to be more severe in CO 2 ‐enriched plots. Positive effects of atmospheric CO 2 enrichment on mycorrhizal fungi, primarily observed in deeper soil, are probably contributing to the prolonged stimulation of NPP by CO 2 enrichment at the Duke FACE study site.

Patterns of prey use by lesser scaup Aythya affinis (Aves) and diet overlap with fishes during spring migration - Kimberly A. Strand; Steven R. Chipps; Sharon N. Kahara; Kenneth F. Higgins; Spencer Vaa (Hydrobiologia, 2008)

Does increased abundance of sea lice influence survival of wild Atlantic salmon post‐smolt? - N. A. Hvidsten; B. Finstad; F. Kroglund; B. O. Johnsen; R. Strand; J. V. Arnekleiv; P. A. Bjørn (Journal of Fish Biology, 2007)
A synthesis of results from two projects was assessed to analyse possible influence of sea lice Lepeophtheirus salmonis on marine Atlantic salmon Salmo salar survival. During the years 1992–2004, trawling for wild migrating post‐smolts was performed in Trondheimsfjord, a fjord in which no Atlantic salmon aquaculture activity is permitted. Prevalence and intensity of sea lice infections on migrating wild post‐smolts differed between years. A correlation analysis between 1 sea‐winter (SW) Atlantic salmon catch statistics from the River Orkla (a Trondheimsfjord river) and sea lice infections on the migrating smolts in the Trondheimsfjord was not significant. Up to 2% reduction in adult returns due to sea‐lice infection was expected. In addition, experimental releases from 1996 to 1998 with individually tagged groups of hatchery‐reared Atlantic salmon smolts given protection against sea‐lice infection was performed. Higher recaptures of adult Atlantic salmon from 1998 treated smolts compared to the control group may correspond to high abundance of sea lice found on the wild smolt, and may indicate influence on post‐smolt mortality. These studies indicate that post‐smolt mortality in Trondheimsfjord is marginally influenced by sea lice infection; however, the methods for assessing wild smolt mortality might be insufficient. Higher infections of sea lice farther out in the fjord may indicate more loss in Atlantic salmon returns in some years.

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.

Examples of high-frequency EPR studies in bioinorganic chemistry - K. Kristoffer Andersson; Peter P. Schmidt; Bettina Katterle; Kari R. Strand; Amy E. Palmer; Sang-Kyu Lee; Edward I. Solomon; Astrid Gräslund; Anne-Laure Barra (JBIC Journal of Biological Inorganic Chemistry, 2003)

Parallel climate model (PCM) control and transient simulations - W. M. Washington; J. W. Weatherly; G. A. Meehl; A. J. Semtner Jr.; T. W. Bettge; A. P. Craig; W. G. Strand Jr.; J. Arblaster; V. B. Wayland; R. James; Y. Zhang (Climate Dynamics, 2000)

Constrained oviposition and female-biased sex allocation in a parasitic wasp - P. J. Ode; Michael F. Antolin; Michael R. Strand (Oecologia, 1997)

Superparasitism and ovicide in parasitic Hymenoptera: theory and a case study of the ectoparasitoid Bracon hebetor - M. R. Strand; H. C. J. Godfray (Behavioral Ecology and Sociobiology, 1989)

Oxygen and nitrate reduction kinetics of a nonflocculating strain of Zoogloea ramigera - S. E. Strand; A. J. McDonnell; R. F. Unz (Antonie van Leeuwenhoek, 1988)

Stimulation of oviposition and successful rearing ofTelenomus heliothidis [Hym.: Scelionidae] on nonhosts by use of a host-recognition kairomone - M. R. Strand; S. B. Vinson (BioControl, 1982)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)